The use enzyme immuno assay methode for measurement of milk progresterone without extraction for early pregnancy diagnosis in cow - Adnin Adnan; M. Agus Setiadi; M. Khoeron . (Hemera Zoa, 1995)
An Enzyme Immuno Assay for Progesterone, using horse radish peroxidase as the label, was adapted for direct measurement of progesterone in milk. This was carriedout to detect early pregnancy in cows. The experiment used sixty milking cows divided into three groups, one as a controland two others as treatment groups. In group I (control) milk samples were collected on the day of insemination to 24 days afterward by quartan collection. In group II, milk samples were collected on days 18, 21 and 24 after insemination. In group III, milk samples were collected on days 21 and 24 after insemination. Milk samples were collected from lactating cows at noon from four quarters and preserved with Potassium dichromate (Merck 4858), stored at - 20 degree C until analysed.Pregnancy diagnosis by EIA was confirmed by rectal palpation at 60 to 90 days after insemination. The early pregnancy diagnosis in Group II compared with Group III showed that prolonged the time of sampling indeclinable improved the acuracy.